Performance Of Village Owned Enterprises (BUMDES) Jeruju Berkah in Jeruju Big Village Kubu Raya District (Case Study of the Tourism Business Sector in the Equator Park Area Post Covid 19) - Bima Sujendra; Pabali Musa; Nahot Tua Parlindungan Sihaloho (Yayasan Ilomata, 2023)
This research aims to analyze the Development Strategy for Village-Owned Enterprises (B.U.M.D.E.S.) in Jeruju Berkah, especially in the Tourism Business Sector in the Equator Park Area in Jeruju Besar Village, Kubu Raya Regency, Post-Covid 19. This research is a qualitative descriptive research. The research results show that the establishment of Village-Owned Enterprises (B.U.M.D.E.S.) can be used as a strategy that should be considered in village development efforts and to improve community welfare. Meanwhile, the obstacles are the abandonment of Village-Owned Enterprises in the Equator Park Area Tourism Business Sector during COVID-19, the lack of number of visitors after the Village-Owned Enterprises in the Equator Park Area Tourism Business Sector reopened after COVID-19, and the lack of innovation carried out by the management in promoting Equator Tourism. Park. The efforts of the Jeruju Besar Village Government in overcoming obstacles to Village-Owned Enterprises to improve community welfare include formulating appropriate strategies, building cooperation with local governments, and recruiting competent human resources in the tourism sector.